Operational and Marketing Strategic For Integrated Digital Service Attractiveness: A Study on "Madina" From Bank Muamalat Indonesia - Devi Septiana; Marissa Grace Haque; Batara Maju Simatupang; Bambang Budhijana (Journal Research of Social Science, Economics, and Management, 2024)
Technological developments are forcing the banking sector to adapt to the digital era. Bank Muamalat Indonesia focuses on e-Banking services for non-individual customers. 24/7 service, including the MADINA feature for real-time transactions, makes things easier for customers. MADINA, a CMS application, makes cash management easier for corporate customers. Through SWOT and QSPM analysis, the bank formulates a digital marketing strategy to improve business performance. This research uses mixed methods, combining quantitative and qualitative data to produce a narrative description. This approach emphasizes the nature of data, process rather than results. Descriptive analysis was carried out using a financial ratio approach. The focus is on converting qualitative data into quantitative data from interviews as a data collection technique. Bank Muamalat Indonesia will implement a collaboration strategy with third parties as a top priority, with the highest TAS of 4,143. The second alternative is to utilize brand image, with TAS 4,068. Utilization of technology in promotions was the third highest strategy, with TAS 4,031, followed by sustainable satisfaction for partners with TAS 4,003. Training to improve the quality of human resources is the final strategy with a TAS weight of 4.031.